Peningkatan Hasil Tanaman Kedelai melalui Pemberian Pupuk Organik Cair Biourin dan Dosis Pupuk Fosfat - SUPADMA, A.A. NYOMAN; PUJA, I NYOMAN; MEGA, I MADE (Agrotrop : Journal on Agriculture Science; Vol 4 No 2 (2014))
An Increase of The Yield of Soybean with Application of Biorine and Phosphorous Fertilizers. The experiment was conducted at green house of the Field Laboratory of Faculty of Agriculture, Udayana University, located at Pegok Denpasar. The Randomized Block Design (RBD) was arranged with three replications and nine treatments. The treatments namely : A (400 ml biourine L-1 water + 0 kg SP-36 ha-1), B (350 ml biourine L-1 water + 25 kg SP-36 ha-1), C (300 ml biourine L 1 water + 50 kg SP-36 ha-1), D (250 ml biourine L-1 water + 75 kg SP-36 ha), E (200 ml biourine L-1 water + 100 kg SP-36 ha-1), F (150 ml biourine L-1 water) + 125 kg SP-36 ha-1, G (100 ml biourine L-1 water + 150 kg SP-36 ha-1), H (50 ml biourine L-1 water + 175 kg SP-36 ha-1), I (0 ml biourine L-1 water + 200 kg SP-36 ha-1). The statistical analysis showed the treatments had significant effects on the variable of the weight of grain dry oven, 12% of water-containing weight of grain, and estimation of yields of 12% of water-containing weight of grain per hectar, but not significant to the number of nodule, height of plant, weight of plant, and weight of grains at post harvest. The highest yields of soybean was found on E treatment (37,30 ku ha 1).
Keywords: consentration of biourine, dosage fosfat, yields of soybean